Kajian Kesalingan: Emansipasi Laki-Laki dan Perempuan di Ranah Publik pada Era Kontemporer dalam Perspektif Al-Qur’an - M Bintang Fadhlurrahman; Naqiyah Mukhtar; Shofia Nur Aini; Hikmatul Siti Masitoh (Jurnal Riset Agama, 2022)
This study aims to understand the meaning of the struggle for emancipation and social rights for men and women in the contemporary era which is studied through the Qiraah Mubadalah or mutuality method. This research is a type of qualitative research in data analysis in the form of document studies and scientific journal data. Researchers also took information from various articles in the media to strengthen this research. The result of this research is that gender equality and justice is the result of the thoughts of the initiators and bearers of world peace. Through the Qiraah Mubadalah method or the study of mutuality, justice and gender equality are seen in Islam. This study also concludes that gender equality and justice is the result of the thoughts of the initiators and advocates of world peace. Through the Qiraah Mubadalah method or the study of mutuality, justice and gender equality are seen in Islam. Islam calls for goodness and justice, Islam is also a religion that comes by glorifying women and men without exception.